2008
DOI: 10.1164/rccm.200710-1544oc
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Food Consumption during Pregnancy and the Longitudinal Development of Childhood Asthma

Abstract: Results of this study indicate an increased risk of daily versus rare consumption of nut products during pregnancy on childhood asthma outcomes. These findings need to be replicated by other studies before dietary advice can be given to pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 36 publications
2
131
1
2
Order By: Relevance
“…At least one serve a fish a week by mothers during pregnancy was protective for eczema in their children at five years of age in one study, while none of the other foods tested (including fruit and vegetables, grains and fats) showed any consistent associations [58]. One study [60] also found no association between vitamin D from food consumed during pregnancy and development of eczema in children at five years of age.…”
Section: Observational Studiesmentioning
confidence: 89%
“…At least one serve a fish a week by mothers during pregnancy was protective for eczema in their children at five years of age in one study, while none of the other foods tested (including fruit and vegetables, grains and fats) showed any consistent associations [58]. One study [60] also found no association between vitamin D from food consumed during pregnancy and development of eczema in children at five years of age.…”
Section: Observational Studiesmentioning
confidence: 89%
“…These observations are in contrast to results from previous studies, which mainly, but not consistent, suggest that maternal fish intake during pregnancy protects against the development of childhood asthma and atopy. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Observational studies in large cohorts observed lower incidence of eczema in offspring of mothers with the highest fish consumption during pregnancy, 19,21 but not lower incidences of wheezing or asthma. In the Netherlands, fish consumption is relatively low, which can explain the differences in the observations.…”
Section: Maternal Fish Consumption and Atopic Symptoms Etm Leermakersmentioning
confidence: 98%
“…22 It is difficult to determine whether the suggested beneficial effects that were observed in previous observational studies were due to fish consumption and not to other aspects from maternal diet or lifestyle. None of the previous studies that found an association of maternal fish consumption during pregnancy with childhood asthma did take maternal body mass index, folic acid supplement use, alcohol use and distress during pregnancy into account.…”
Section: Maternal Fish Consumption and Atopic Symptoms Etm Leermakersmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] Several observational studies have reported protective associations between increased fish intake in pregnancy and allergic disease symptoms in offspring from infancy to 6 years of age. [9][10][11][12][13][14] However, these observational studies are unable to establish causality because of the difficulty in adjusting for complex confounding factors. 15 Randomized controlled trials (RCTs) of n-3 LCPUFA supplementation during pregnancy have reported protective effects; however, apart from 1 16-year registry based follow-up, 16 all reported allergic disease outcomes are in early childhood (between 1 and 3 years of age).…”
mentioning
confidence: 99%